Blood DNA methylation signatures are associated with social determinants of health among survivors of childhood cancer. Issue 11 (2nd November 2022) - Song, Nan; Sim, Jin-Ah; Dong, Qian; Zheng, Yinan; Hou, Lifang; Li, Zhenghong; Hsu, Chia-Wei; Pan, Haitao; Mulder, Heather; Easton, John; Walker, Emily; Neale, Geoffrey; et al.
ABSTRACT: Social epigenomics is an emerging field in which social scientist collaborate with computational biologists, especially epigeneticists, to address the underlying pathway for biological embedding of life experiences. This social epigenomics study included long-term childhood cancer survivors enrolled in the St. Jude Lifetime Cohort. DNA methylation (DNAm) data were generated using the Illumina EPIC BeadChip, and three social determinants of health (SDOH) factors were assessed: self-reported educational attainment, personal income, and an area deprivation index based on census track data. An epigenome-wide association study (EWAS) was performed to evaluate the relation between DNAm at each 5'-cytosine-phosphate-guanine-3' (CpG) site and each SDOH factor based on multivariable linear regression models stratified by ancestry (European ancestry, n = 1, 618; African ancestry, n = 258). EWAS among survivors of European ancestry identified 130 epigenome-wide significant SDOH–CpG associations ( P < 9 × 10 −8 ), 25 of which were validated in survivors of African ancestry ( P < 0.05). Thirteen CpGs were associated with all three SDOH factors and resided at pleiotropic loci in cigarette smoking–related genes (e.g., CLDND1 and CPOX ). After accounting for smoking and body mass index, these associations remained significant with attenuated effect sizes. Seven of 13 CpGs were associated with gene expression level based on 57 subsamples with blood RNA sequencing data available. In conclusion, DNAm signatures, many resembling the effect of tobacco use, were associated with SDOH factors among survivors of childhood cancer, thereby suggesting that biologically distal SDOH factors influence health behaviours or related factors, the epigenome, and subsequently survivors' health.